DesiCrit and Adult Education: Adding Masala to CRT - Edith Gnanadass (Adult Education Research Conference, 2025)
Drawing on qualitative data on how South Asian Americans learned to become racialized in the US, this paper explores Desicrit, an offshoot of CRT, to decolonize adult learning and practice.
Keywords: CRT and adult education; DesiCrit and adult learning; decolonizing adult education